2013
DOI: 10.4238/2013.january.4.14
|View full text |Cite
|
Sign up to set email alerts
|

High leptin level and leptin receptor Lys656Asn variant are risk factors for preeclampsia

Abstract: ABSTRACT. The aim of this study was to investigate the relationship between the leptin receptor (LEPR) polymorphism/serum leptin level and preeclampsia. The prevalence of a single nucleotide polymorphism in the LEPR gene exon 14 at -656 and the serum leptin concentrations in 97 preeclamptic pregnant mothers were compared to those of 110 healthy controls. The Lys656Asn genotype and Lys656Asn + Asn656Asn frequencies in the LEPR gene were significantly more prevalent in preeclampsia mothers than in controls (P < … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…They have poor reproductive outcomes in natural as well as assisted conception . Several LEPR SNPs were found to be associated with obesity phenotypes, insulin resistance, hypertension, renal cell carcinoma, lung cancer, dyslipidemia, pre‐eclampsia, idiopathic recurrent pregnancy loss, and decrease in ovulation and/or luteinisation resulting in various physiopathological phenotypes and diminished reproductive development in human.…”
Section: Introductionmentioning
confidence: 99%
“…They have poor reproductive outcomes in natural as well as assisted conception . Several LEPR SNPs were found to be associated with obesity phenotypes, insulin resistance, hypertension, renal cell carcinoma, lung cancer, dyslipidemia, pre‐eclampsia, idiopathic recurrent pregnancy loss, and decrease in ovulation and/or luteinisation resulting in various physiopathological phenotypes and diminished reproductive development in human.…”
Section: Introductionmentioning
confidence: 99%
“…The Table 3 shows a comparison of allele frequencies of both variants c.668A>G and c.1968G>C in our studied populations and other studies from Hungary, Germany, Sri -Lanka, and China [18][19][20][21]34]. The frequency of allele G in the variant c.668A>G in our study group (26.9) was slightly lower than in the Sri-Lankan population (35.8) and much lower than in the global allele frequency (44.9), Hungarian population (42.5) and German population (57.3).…”
Section: Resultsmentioning
confidence: 93%
“…Furthermore, Wang et. al., reported a significant association of LEPR c.C1968 homozygous + LEPR c.G1968 heterozygous with preeclampsia in a Chinese population [19]. The LEPR c.1968G>C variant led to a change of G to C at nucleotide c.1968 in exon 14.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Also, it has been reported that hypoxia was associated with an increase expression of a group of leptin genes in trophoblastic cells (4). HA associated hypoxia increases the Ob (Lep) gene expression and the LEPR gene expression in preeclamptic mothers (24). Involvement of leptin in pathogenesis of PE has been previously investigated.…”
Section: Discussionmentioning
confidence: 99%